ANALISIS METODE CIRC (COORPERATIVE INTEGRETED READING AND COMPOSITION) TERHADAP PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SEKOLAH DASAR - Mutiara Anifah; Sofhie Ekanissa Rahma Ayu (Universitas Negeri Medan, 2023)
This study aims to describe the reading comprehension skills of fifth grade students of SD Islam Harapan Ibu by using the CIRC method. This research used descriptive qualitative research design. This research uses observation, interview, and documentation as data accumulation methods. Data reduction, data presentation, and conclusion drawing are the data analysis approaches used. In this research that uses the CIRC (Cooperative Integrated Reading and Composition) method, it shows an increase in students' reading comprehension skills. This can be proven through the results of the LKPD work done in groups by students, as well as the ability of students to present the results of their discussions and the value of reading comprehension skills that increase. This CIRC method is very effective and very suitable for developing students' reading comprehension skills in Indonesian language lessons in grade V students of SD Islam Harapan Ibu.